Characterizing the Roles of AI-Enabled Non-Human Agents in Service Systems - Wilga, Matthäus; Hajjam, Layla; Lugmair, Nina; Schymanietz, Martin; Roth, Angela (19th International Conference on Wirtschaftsinformatik, 2024)
Machines are becoming more versed at adapting to environmental impulses and their operational contexts, changing their roles in service systems. These machines can autonomously fulfill goals within defined boundaries set by legal actors and thereby exhibit agency. As interactions are at the core of services, the integration of such non-human agents into value co-creation has the potential to heavily impact the innovation of services. Following a four-step type construction approach based on empirical open-source data on 130 services, we develop a multi-dimensional characterization of six roles that non-human agents fulfill in service systems. Taking a systemic perspective, we identify service system interactions involving non-human agents and how their contributions impact value propositions. Our findings forward the understanding of service processes involving non-human agents and their impact on value co-creation, benefiting both theory and practice through knowledge on the engineering of service systems and value-driven, user-centered human-machine interaction

HARMONIZING INNOVATION PROCESSES - Hajjam, Layla; Koustas, Spyridon Georg; Kurtz, Julian; Lugmair, Nina (2023)